FIXED TARGET TRAINING: MENINGKATKAN AKURASI SPIKE ANGGOTA UKM BOLA VOLI STKIP BINA MUTIARA SUKABUMI - Debi Krisna Irawan; Rafdlal Saeful Bakhri; Ismy Antafani ($$8@@&&$%K, 2023)
The techniques used to attack or score in sports games are important techniques to master. The spike technique in volleyball is carried out with the main objective of producing a score in order to win. The ball that is hit in the spike technique, besides having to be strong and fast, of course, must be directed at an empty area or difficult for the opponent to anticipate. Good spike accuracy is one of the key factors in volleyball, which can contribute to the team's success in scoring points. Therefore proper training is needed to be able to improve volleyball spike skills. This study aims to investigate the effect of fixed target training on increasing the spike accuracy of members of the Volleyball UKM STKIP Bina Mutiara Sukabumi. This study used an experimental method through the One-Group Pretest Posttest design. The research sample consisted of 10 members of STKIP Volleyball UKM Bina Mutiara Sukabumi who were selected by purposive sampling and received fixed target training. The research data were obtained using the volleyball spike test which was carried out at the pretest and posttest stages. The results of data analysis through paired sample t test showed that the p value <0.05. Based on this, it was stated that fixed target training had a positive and significant effect on the results of the spike accuracy of members of the STKIP Volleyball UKM Bina Mutiara Sukabumi.